The Vertical Profile of Phosphate on the Bakuok Lake in Aursati Village Tambang Subdistrict Kampar District Riau Province - July Prenky Purba; Madju Siagian2; Asmika H. Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research has been done on the Bakuok Lake in Aursati Village Tambang Subdistrict District Kampar in March - April 2014. This research aims to understand the vertical profile of phosphate in this reservoir. The research used survey method. The sample’s were taken from three station and vertically in three sampling point. The parameters of water quality measured were observed pH, dissolved oxygen (DO), brightness, temperature and depth. Sampling vertical based on transparency, namely at surface, 11/2 Secchi depth and in the bottom of lake. The result shown the concentration of phosphate at the surface: 0,01 mg/L – 0,03 mg/L; in the 11/2 Secchi depth; 0,04 mg/L – 0,09 mg/L; and the bottom of lake: 0,09 mg/L – 0,17 mg/L. The vertical profile of phosphate showed the concentration increased with the increment of depth. The water quality parameter were temperature 29,6oC – 30oC; transparancy 74,3 cm – 93,7 cm; depth: 208 cm – 332 cm; pH: 6 and dissolved oxygen (DO): 1,78 mg/L – 5,33 mg/L. The concentration of phosphate in Bakuok Lake showed the tropic status was mesotropic and all the water quality still support the aquatic organisms life.Keywords : Phosphate, the vertical profile, Bakuok Lake